Optimal ski jump
Gale force winds, a 60-kilo test dummy, and one of Norway`s largest wind tunnels are helping researchers at the Norwegian University of Science and Technology perfect the optimal ski jump. Next year Tommy Ingebrigtsen and the other members of Norway`s national ski jumping team could have new ski boots as a result. With some information about this wind tunnel. see also: http://geminiresearchnews.com/2003/11/optimal-ski-jump/